EDUCATION ON THE IMPORTANCE OF THE FIRST 1000 DAYS OF LIFE IN AN EFFORT TO IMPROVE THE NUTRITIONAL STATUS OF CHILDREN IN THE WORKING AREA OF PUSKESMAS KARTINI, PEMATANG SIANTAR CITY - Yunardi (PT. Radja Intercontinental Publishing, 2021)
Community service activities carried out in the form of education on the importance of the First 1000 Days of Life in improving the health and nutritional status of children in the Working Area of ​​the Kartini Health Center, Pematang Siantar City. The partner in this activity is the Kartini Health Center with the target being pregnant women and mothers with toddlers who come to the Posyandu in the Working Area of ​​the Kartini Health Center in Pematang Siantar City. The choice of location for the activity was because the Kartini Health Center is one of the Health Centers in the city center of Pematang Siantar. Nutritional and health problems, especially in toddlers, can be prevented through educational activities provided through Posyandu activities. The solution in community service activities is to provide education on the First 1000 Days of Life for parents of toddlers, specifically mothers who come to visit the Posyandu. The purpose of this service activity is to increase the knowledge of parents of toddlers about the First 1000 Days of Life and changes in good nutritional behavior so that they can improve the health and nutritional status of children. The benefit of this activity is that parents, especially pregnant women and mothers of toddlers, know the importance of the First 1000 Days of Life to prevent nutritional problems in toddlers and improve children's health and nutritional status. The purpose of this service activity is to increase the knowledge of parents of toddlers about the First 1000 Days of Life and changes in good nutritional behavior so that they can improve the health and nutritional status of children. The benefit of this activity is that parents, especially pregnant women and mothers of toddlers, know the importance of the First 1000 Days of Life to prevent nutritional problems in toddlers and improve children's health and nutritional status. The purpose of this service activity is to increase the knowledge of parents of toddlers about the First 1000 Days of Life and changes in good nutritional behavior so that they can improve the health and nutritional status of children. The benefit of this activity is that parents, especially pregnant women and mothers of toddlers, know the importance of the First 1000 Days of Life to prevent nutritional problems in toddlers and improve children's health and nutritional status. The expected output of community service activities is in the form of articles published in community service journals and leaflets.